Underreaction to Political Information and Price Momentum. Issue 3 (20th August 2018) - Addoum, Jawad M.; Delikouras, Stefanos; Ke, Da; Kumar, Alok
Abstract: In this study, we examine whether momentum in stock prices is induced by changes in the political environment. We find that momentum profits are concentrated among politically sensitive firms and industries. From 1939 to 2016, a trading strategy with a long position in winner portfolios (industries or firms) that are politically unfavored and a short position in losers that are politically favored does not generate significant momentum profits. Furthermore, our political‐sensitivity‐based long‐short portfolio explains 23% to 27% (42% to 43%) of monthly stock (industry) momentum alphas. This explanatory power is concentrated around presidential elections, when the level of political activity is high. Collectively, our results suggest that investor underreaction to political information generates momentum in stock and industry returns.